Pengaruh Model Concept Sentence dengan Pendekatan CLIL terhadap Pengetahuan dan Keterampilan Krangan Narasi Kelas V - ratna sari; Abdul Muktadir; Daimun Hambali (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2021)
This study aims to determine the effect of the concept sentence model with the CLIL approach to the knowledge and skills of writing narrative essays in class V of the Rejang Lebong V. group This type of research is quantitative research using the Quasi Experimental Research method with One Group Pretest and Posttest Design. The population in this study were all fifth grade students of Rejang Lebong Public Elementary School grade A accredited A, totaling 222 students, namely SDN 110, SDN 111, and SDN 114. The sampling technique was using cluster random sampling. The sample in this study consisted of 1 study group, which was an experimental class consisting of 32 students from 111 Rejang Lebong Elementary Schools. The research instrument was used in the form of a 5W + 1H narrative essay knowledge and writing skill given through the pre-test before the learning took place and the post-test after the learning took place. The research data were analyzed using descriptive analysis, prerequisite tests, and inferential analysis, namely one sample t-test. Data were obtained from the results of the study of the average pretest experimental class knowledge (53) and the average pretest experimental class skills (42). While the research data of posttest average experimental class knowledge (68) and posttest average experimental class skills (69). One sample of the results of the t-test is knowledge of the posttest value indicating sig. (2-tailed) (0.468)> ? (0.05). For this reason Ho was rejected. And for the posttest test sample the narrative essay writing skills show sig. (2-tailed) (0.552)> ? (0.05). For this reason Ho was rejected. Because both hypotheses are Ho which is rejected, which means Ha is accepted. Thus it can be concluded that there is an effect of the application of the concept of sentence learning models with the CLIL approach to the knowledge and skills of writing narrative essays in class V SDN Group V Rejang Lebong. The difference is shown after students follow the narrative text learning by applying the concept of sentence learning models with the CLIL approach.